ANALISIS BIAYA PRODUKSI DAN PENGELOLAAN PERSEDIAAN PADA PERUSAHAAN PT NOORE SPORT INDONESIA DI KOTA BANDUNG - Febrianti, Keukeu Safitri; AR, Rasmawati (Jurnal Ekualisasi, 2024)
Effective production cost management is crucial for determining competitive selling prices, especially when facing competitors offering similar products at affordable prices. Inventory management plays a vital role in the sales process, making it essential for companies to manage and monitor their inventory effectively. This research addresses the challenges faced by companies regarding suboptimal production cost calculations and inadequate inventory management, leading to stock shortages. The study aims to analyze the practices employed by companies to optimize production costs and manage inventory efficiently, thereby maintaining product quality and responding to market changes. The focus is on understanding how companies identify, measure, and control production costs and manage inventory efficiently. The research employs descriptive and quantitative methods, including observations, interviews, and documentation related to production cost reports and inventory data. The findings indicate that current company policies are not optimal and lack efficiency. This study compares the company's production cost calculations with the full costing method and applies the Economic Order Quantity (EOQ) method for inventory management to enable efficient inventory control. The implications suggest that adopting these methods can significantly improve production cost management and inventory efficiency, providing a competitive edge in the market